2021
DOI: 10.1016/j.ajur.2020.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Age-specific reference ranges of prostate-specific antigen in the elderly of Amirkola: A population-based study

Abstract: Objective To determine the age-specific reference ranges of prostate-specific antigen (PSA) in the older men in the city of Amirkola. Methods This cross-sectional study is a part of Amirkola Health and Ageing Project (AHAP) which has been conducted as a cohort study since 2011 in Amirkola, a city in northern Iran. The demographic information of all men aged 60 and older were collected through questionnaires and interviews and the PSA measurements were performed using EL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…Both in rural and in urban areas, PSA level increases with age, which agrees with what has been published by other authors [21]. In our study, men from rural areas had higher PSA comparing with men of urban area, which is a new finding since there are no studies that compare PSA levels in men who live in rural area compared to men who live in urban area in our environment.…”
Section: Diagnosis Of Prostate Diseasesupporting
confidence: 92%
“…Both in rural and in urban areas, PSA level increases with age, which agrees with what has been published by other authors [21]. In our study, men from rural areas had higher PSA comparing with men of urban area, which is a new finding since there are no studies that compare PSA levels in men who live in rural area compared to men who live in urban area in our environment.…”
Section: Diagnosis Of Prostate Diseasesupporting
confidence: 92%
“…Prostatespecific antigen level is correlated with age and as age increases, PSA level also becomes higher. 20 This relationship can be explained by the fact that there is age related increase in the prevalence of benign prostatic enlargement. 21 Our study found that the mean PSA level increased with age )3.41±4.67 ng/dL(, especially in those aged 80 years and older.…”
Section: Resultsmentioning
confidence: 99%
“…We are conscious of different limitations of our study. First, the retrospective nature of our work, associated with the relatively limited sample size, does not permit drawing certain conclusions; secondly, the absence of a stratified PSA according to the age of patients, which, if one on side could have been an interesting aspect of our work, could have further limited the recruited sample size in smaller groups; thirdly, we assumed as a normal PSA a mean value <4 ng/mL which could not be associated with older patients [49][50][51][52][53]. We aim to evaluate these aspects and resolve these pitfalls in the next study.…”
Section: Discussionmentioning
confidence: 99%